A photoactive iridium(III) complex with 3-methyl-2-phenyl pyridine and 1, 1-bis(diphenylphosphino)methane: Synthesis, structural characterization and cytotoxicity in breast cancer cells. Issue 14 (18th July 2021) - Leesakul, Nararak; Kullawanichaiyanan, Keerati; Mutić, Sanja; Guzsvány, Valéria; Nhukeaw, Tidarat; Ratanaphan, Adisorn; Saithong, Saowanit; Konno, Takumi; Sirimahachai, Uraiwan; Promarak, Vinich
Abstract: A photoactive complex [Ir(3m-ppy)2 (dppm)Cl] (1 ; dppm = bis(diphenylphosphino)methane, 3 m-Hppy = 3-methyl-2-phenylpyridine), which shows a green luminescence band at 517 nm in DMSO was synthesized from reaction of the dimeric [Ir2 (3m-ppy)4 Cl2 ] with dppm under an inert atmosphere. Complex 1 was characterized by 1 H NMR, FT-IR, ESI-MS spectroscopies and CHN analysis. Single-crystal X-ray analysis of 1 revealed a distorted octahedral geometry comprising an Ir III center with monodentate dppm, bidentate-C, N 3 m-ppy and chlorido ligands. The electrochemistry of 1 was studied by cyclic voltammetry in 0.1 M NaClO4 in acetonitrile on a glassy carbon working electrode, displaying an oxidation peak of Ir III / IV at 1.2 V. Complex 1 showed anticancer activity against MDA-MB-231, MCF-7 and HCC1937 cell lines of human breast cancer; the respective cytotoxicity factors of 160, 32 and 25 were significantly greater than the cytotoxicity factors obtained with cisplatin. Abstract : UF0001